POST-PANDEMIC ECONOMIC RECOVERY: ASSESSMENTS OF THE STABILITY OF GLOBAL MACROECONOMIC SYSTEMS - Владислав Полянський (Економіка та суспільство, 2025)
The article provides a comprehensive assessment of the stability of global macroeconomic systems in the post-pandemic period with a focus on the impact of the COVID-19 pandemic. The dynamics of macroeconomic indicators in the period from 2001 to 2025, including the pre-crisis, crisis, post-crisis and post-COVID stages, are considered. The results of the analysis showed that the pandemic significantly worsened the macroeconomic stability of most countries, increasing the share of countries with a low level of stability in the post-COVID period. At the same time, the share of countries with a high level of stability decreased which indicates the growing vulnerability of even the most developed economies. Clear structural shifts were observed in the distribution of countries by level of stability which indicates a reassessment of traditional development models. The practical value of the article lies in the formation of approaches to monitoring, modeling and forecasting macroeconomic stability in the context of global crises.